A rapid, accurate, and low-cost method for detecting Mycobacterium tuberculosis and its drug-resistant genes in pulmonary tuberculosis: Applications of MassARRAY DNA mass spectrometry - Yang, Han; Li, Aifang; Dang, Liyun; Kang, Tao; Ren, Fei; Ma, Jinbao; Zhou, Yong; Yang, Yuanli; Lei, Jing; Zhang, Tao (Frontiers in Microbiology, 2023)
Introduction Mycobacterium tuberculosis (MTB) identification and drug resistance diagnosis are very important for treatment of drug-resistant tuberculosis (DR-TB). Therefore, high throughput, accurate and low-cost molecular detection techniques are urgently needed. This study aimed to evaluate the clinical application value of MassARRAY in tuberculosis diagnosis and drug resistance screening. Methods The limit of detection (LOD) and clinical application value of MassARRAY were evaluated using reference strains and clinical isolates. MTB in bronchoalveolar lavage fluid (BALF) and sputum samples were detected using MassARRAY, quantitative real-time polymerase chain reaction (qPCR) and MGIT960 liquid culture (culture). Using culture as the standard, the efficacy of MassARRAY and qPCR for the detection of TB was analyzed. Mutation of drug resistance genes in MTB clinical isolates was tested using MassARRAY, high-resolution melting curve (HRM), and Sanger sequencing. Using sequencing as the standard, the efficacy of MassARRAY, and HRM for the detection of each drug resistance site of MTB was analyzed. Simultaneously, the mutation of drug resistance genes by the MassARRAY method was compared with the results of drug susceptibility testing (DST), and the genotype–phenotype relationship was analyzed. The ability of MassARRAY to discriminate mixed infections was detected using mixtures of standard strains (M. tuberculosis H37Rv) and drug-resistant clinical isolates and mixtures of wild-type and mutant plasmids. Results In MassARRAY, 20 related gene mutations could be detected by two PCR systems. All genes could be accurately detected when the bacterial load was 104 CFU/mL. When the load of wild-type and drug-resistant MTB mixture was 105 CFU/mL (respectively reached 104 CFU/mL), variants and wild-type genes could be detected simultaneously. The sensitivity of MassARRAY (96.9%) for identification was higher than that of qPCR (87.5%) (p < 0.001). The sensitivity and specificity of MassARRAY for all drug resistance gene mutations were 100.0%, with higher accuracy and consistency than HRM (sensitivity = 89.3% and specificity = 96.9%, p = 0.001). Analyzing the relationship between MassARRAY genotype and DST phenotype, the accuracy of katG_315, rpoB_531, rpsL_43, rpsL_88, and rrs_513 sites was 100.0%, and embB_306 and rpoB_526 were inconsistent with the DST results when the base changes were different. Discussion MassARRAY can obtain base mutation information and identify heteroresistance infections simultaneously when the mutant proportion was at least 5–25%. It has good application prospects in the diagnosis of DR-TB with high throughput, accurate and low-cost.